Pengaruh Penambahan Pecahan Kaca Sebagai Bahan Pengganti Agregat Halus dan Penambahan Fiber Optik Terhadap Kuat Tekan Beton Serat - Ikhsan, Muhammad Nur; Prayuda, Hakas; Saleh, Fadillawaty (Semesta Teknika, 2016)
Fibre concrete is an innovation of normal concrete to special concrete to be stronger withstands the tensile force. Fibre concrete consists of cement, water, fine aggregate, coarse aggregate and additional fibre materials. The addition of fibre is expected to reduce the segragation and prevent cracks of the concrete. In this research used additional glass fracture with variation of 15%, 20%, 25% to the weight of the fine aggregate as well as additional of optic fibre of 0,15% of the concreteâs weight. Their compressive strength was examined at the age of 28 days. The result is gained by adding 15% of glass fracture 24,94 MPa with modulus of elasticity 23471,8 MPa, addition of 20% gained the result of compressive strength by 25,48 MPa with modulus of elasticity 23724,5 MPa, meanwhile by adding glass fracture 25% gained the result of compressive strength 25,77 MPa with modulus of elasticity 23859,2 Mpa.